Metode Dakwah Kepada Masyarakat Multikultural Berdasarkan Qur’an Surat Al-Hujurat - Irfan Syuhudi; Maratua Hasonangan Harahap; Canra Krisna Jaya (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
Surah Al-Hujurat in the Qur'an offers important guidance on social ethics, morals, and ways of interacting that are highly relevant for da'wah in multicultural societies. This study aims to explore da'wah methods based on the principles contained in Surat Al-Hujurat in fostering harmony, respecting differences, and strengthening social cohesion in a diverse society. This study uses qualitative methods and exegetical analysis, analyzing related verses on effective communication, respect for the identity of other groups, as well as prohibitions against negative behaviors such as gossip and prejudice. The results of this study indicate that the Surat Al-Hujurat-based da'wah approach can be a practical solution for creating harmonious relationships in a multicultural society through values that promote tolerance, civility, and peace.